Peste des Petits Ruminants Virus Exhibits Cell-Dependent Interferon Active Response - Tang, Jingyu; Tang, Aoxing; Du, Hanyu; Jia, Nannan; Zhu, Jie; Li, Chuanfeng; Meng, Chunchun; Liu, Guangqing (Frontiers in Cellular and Infection Microbiology, 2022)
Peste des petits ruminants (PPR) is an acute and highly pathogenic infectious disease caused by peste des petits ruminants virus (PPRV), which can infect goats and sheep and poses a major threat to the small ruminants industry. The innate immune response plays an important role as a line of defense against the virus. The effect of PPRV on the active innate immune response has been described in several studies, with different conclusions. We infected three goat-derived cell lines with PPRV and tested their innate immune response. PPRV proliferated in caprine endometrial epithelial cells (EECs), caprine skin fibroblasts cells (GSFs), and goat fibroblast cells (GFs), and all cells expressed interferon (IFN) by poly (I: C) stimulation. PPRV infection stimulated expression of type I and type III IFN on EECs, and expression of the latter was significantly stronger, but IFN was not stimulated in fibroblasts (GSFs and GFs). Our results suggested that the effect of PPRV on IFN was cell-type specific. Nine IFN-stimulated genes (ISGs) were detected in EECs, but only ISG15 and RSAD2 were significantly upregulated. The effects of PPRV on IFN and IFN-induced ISGs were cell-type specific, which advances our understanding of the innate immune response induced by PPRV and creates new possibilities for the control of PPRV infection.